Didactic system of university technical complex - Olga A. Sotnikova; Nikolay S. Fedotov; Oksana I. Belyaeva (Высшее образование в России)
The article describes the benefits of a university complex as a form of higher education institution. The necessity of forming a directional didactic system of a university technical complex is substantiated. There is proposed an approach to the formation of such a system through an additional teachers’ training, based on the project method.